PENGARUH LINGKUNGAN KERJA DAN KIPEMIMPINAN KEPALA SEKOLAH TERHADAP MOTIVASI GURU DI GUGUS I KECAMATAN AMPANA TETE KABUPATEN TOJO UNA-UNA - Ranya, Zulham A. (Katalogis, 2017)
The aims of the study are: 1) to explore and analyze simultaneous influence of work environment and leadership of the principal on motivation of teachers’ in Cluster 1 Ampana Tete Sub-District of Tojo Una-Una; 2) to explore and analyze the influence of work environment on motivation of teachers’ in Cluster 1 Ampana Tete Sub-District of Tojo Una-Una; 3) to explore and analyze the influence of leadership of the principal on motivation of teachers’ in Cluster 1 Ampana Tete Sub-District of Tojo Una-Una. The study is descriptive quantitative and includes 85 teachers as respondents who selected with census method. The results of multiple linear regressions analysis show that: 1) work environment and leadership of the principal simultaneously influence motivation of teachers’ in Cluster 1 Ampana Tete Sub-District of Tojo Una-Una; 2) work environment positively and significantly influence motivation of teachers’ in Cluster 1 Ampana Tete Sub-District of Tojo Una-Una; 3) leadership of the principal positively and significantly influence motivation of teachers’ in Cluster 1 Ampana Tete Sub-District of Tojo Una- Una.